Characterization of metabolically quiescent Leishmania parasites in murine lesions using heavy water labeling. - Joachim Kloehn; Eleanor C Saunders; Sean O'Callaghan; Michael J Dagley; Malcolm J McConville (PLoS Pathogens)
Information on the growth rate and metabolism of microbial pathogens that cause long-term chronic infections is limited, reflecting the absence of suitable tools for measuring these parameters in vivo. Here, we have measured the replication and physiological state of Leishmania mexicana parasites in murine inflammatory lesions using 2H2O labeling. Infected BALB/c mice were labeled with 2H2O for up to 4 months, and the turnover of parasite DNA, RNA, protein and membrane lipids estimated from the rate of deuterium enrichment in constituent pentose sugars, amino acids, and fatty acids, respectively. We show that the replication rate of parasite stages in these tissues is very slow (doubling time of ~12 days), but remarkably constant throughout lesion development. Lesion parasites also exhibit markedly lower rates of RNA synthesis, protein turnover and membrane lipid synthesis than parasite stages isolated from ex vivo infected macrophages or cultured in vitro, suggesting that formation of lesions induces parasites to enter a semi-quiescent physiological state. Significantly, the determined parasite growth rate accounts for the overall increase in parasite burden indicating that parasite death and turnover of infected host cells in these lesions is minimal. We propose that the Leishmania response to lesion formation is an important adaptive strategy that minimizes macrophage activation, providing a permissive environment that supports progressive expansion of parasite burden. This labeling approach can be used to measure the dynamics of other host-microbe interactions in situ.